Reflection on metacognition in real life situations: the truth is out there. Issue 1 (2nd January 2018) - Al-Hilawani, Yasser A.
Abstract: This article was prepared to extend the traditional view of metacognition to include the orientation of thematic and common features analyses of events in daily-life interactions. A brief historical development of metacognition was presented and discussed to pave the way for this new orientation. This heuristic conceptualization and direction of metacognition was realized and materialized due to research in deaf education. Metacognition, as presented in this article, dispelled misconceptions about the cognitive ability of individuals who live with deafness. It was viewed impetus for continued research.